O dispositivo da verdade: uma análise a partir do pensamento de Michel Foucault - Benevides, Pablo Severiano (2013)
This research that contains as support and source the thought of the french philosopher Michel Foucault consists of analyzing the dispositive of truth formation. However, this study is not an exegesis of Foulcault’s thought: along this journey other authours were used such as Friedrich Nietzsche and Gilles Deleuze. The first four chapters consist of an anarchaeogenealogical analysis on the dispositive of the truth formation, while the last four is devoted to an analysis of the subjectivization forms that occur inherent to the dispositive of truth. Thus, this work starts questioning the problematizations raised by Foucault about the truth: this is about the truth itself or solely about the systems of truth, or about the truth effects or even about the politics of truth? So, this is the truth itself or simply a set of things taken as truth? Assuming it is indeed the truth itself that is at play, the notion of dispositive actually appears to inscribe the truth in a field of immanence and reality. The next step is an archaeological analysis of an entire philosophical field formed by the Theories of Truth and the philosophies of Plato, Kant, Descartes and Habermas, precisely because they operate with the truth not at the level of immanence, but in the level of transcendence. Thus, the truth appears as thoughtless and the thought restates as naturally inclined to it. Then, it follows a genealogical review about the dispositive of truth which investigates it from the standpoint of the will and the value of truth. Provided with the thought of Nietzsche and Foucault, this analysis shows in what consists the lie of the truth. The third movement moves to the record of an anarchaeological analysis-attitude that implies a rejection of the power of truth, and is when some indispensable notions to the politics of truth are situated: power, resistance, critique, ideology, governmentality. Ended the first step, this study follows on with an analysis of the forms of subjectivity that occur in the immanence of the dispositive of truth, and it starts with a thematization of the subject constitution from the political practice and ethics of parrhesia as well as its consequences on the themes of the care of the self, the true life and the cynicism. The following is an analysis of the antinomies of the educative reason in the dispositive of the truth: a set of conflicting discursive formations which deal with the issues of permanence and purpose of education, as well as the difference between those who teaches and those who are taught. These antinomies were extracted from the principles present in the Christian guidance and in the ancient guidance practices. Subsequently, there is an analysis of the forms of production and extortion of the truth of the self practiced from the psychological field - especially by the ways in which the procedure of confession (aveu) is agencied by it. This work ends with the themes of relationship between the truth of the self and the prison of the self from the subjective positions configured under the sign of autonomy, freedom and authenticity.